STRATEGI PENINGKATAN JUMLAH PELANGGAN LCL IMPOR - Tjetjep Karsafman; Muchammad Iqbal (Institut Transportasi dan Logistik Trisakti, 2016)
PT. FPS (Famous Pacific Shipping) Indonesia is dealing with export and import containers delivery which always needs to innovate to face the competitors. By using SWOT, it is expected that the company could elevate their strength and opportunity and deduce their weakness and threat. The strength factors of PT. FPS Indonesia are wide market share, strategic location, qualified employees, good and strong finance, and has a wide networking. While the weaknesses are the authority of warehousing for stacking, inter department and between branches coordinators, the facilities and infrastructures, and the mapping of career employee. The opportunity factors are the vast development in technology and information, wide networking, good company’s image, the increasing potensial customers, and the Indonesian market policy. On the other hand, the threat factors are the fluctuative world oil price, many competitors, politics situation in Indonesia, tariff exchange, and the fluctuative goods delivery.